Sengketa Amandemen Akta Perdamaian PKPU Homologasi dan Perbandingan dengan Hukum Kepailitan Amerika Serikat (Studi Kasus: Kepailitan PT APOL dan PT Berlian Tangker) - Khairunnisa, Shania; Nefi, Arman (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
There is no provision in Indonesian bankruptcy law that states that the Accord in bankruptcy can be amended outside the court, but in fact this happens. The problem discussed in this research is how the provisions regarding the amendment of the Accord in Indonesia are viewed from theory and applicable law and how this provision is compared in Indonesian and American bankruptcy law. This problem is answered with normative juridical research method. The results showed that amendments to the Accord outside the court cannot be made, although it is not specifically regulated in the Bankruptcy and PKPU Law. The argument is based on the urgency of the court’s role in the process of validating the Accord and based on the systematic interpretation between the Civil Code and the Bankruptcy and PKPU Law. Thus, the existence of an amended Accord outside the court is not binding for debtors and creditors. Furthermore, as a comparison, American bankruptcy law justifies and regulates the amendment of the Accord and the cancellation of the Accord is optional, whereas Indonesia does not regulate and prohibits the amendment of the peace deed because it will eliminate the sanction of canceling the peace deed in the form of imposing bankruptcy status for the debtor. The suggestion on this issue is to provide a clear regulation in Indonesian bankruptcy law on the amendment of Accord, either through amendments to existing laws or through the establishment of implementing regulations.